2016
DOI: 10.21276/ijmrp.2016.2.6.013
|View full text |Cite
|
Sign up to set email alerts
|

Foetal Kidney Length as a Parameter for Determination of Gestational Age in Pregnancy by Ultrasonography

Abstract: Background: The ability to accurately determine the fetal gestational age, growth and recognize its abnormal patterns, help us to decide if early intervention is necessary in high risk pregnancy or not. Objectives: The aim of this present study to estimate the gestational age in third trimester using mean fetal kidney length. Material & Methods: This cross section hospital based study conducted in the department of Obstetrics and Gynecology, S.P. Medical College, Bikaner during study period of one year from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
2
2
1
Order By: Relevance
“…The present work exhibited that the best fit line was with the linear regression equation of: The predicted gestational age from the kidney length = 6.315 + 0.727 X the foetal kidney length ± 1.078. The present finding agrees more or less with Chatterjee et al, [26] and Saxena et al, [5] who reported that the foetal kidney length among Indians could be used as an individual parameter in estimating the gestational age, especially in the later trimesters, where the biometric indices might not be much reliable.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present work exhibited that the best fit line was with the linear regression equation of: The predicted gestational age from the kidney length = 6.315 + 0.727 X the foetal kidney length ± 1.078. The present finding agrees more or less with Chatterjee et al, [26] and Saxena et al, [5] who reported that the foetal kidney length among Indians could be used as an individual parameter in estimating the gestational age, especially in the later trimesters, where the biometric indices might not be much reliable.…”
Section: Discussionsupporting
confidence: 92%
“…The crude values of the means of the AFI ± 2SD according to the gestational ages were represented in Chart (4). The 5 th, 50th and 95 th percentiles of the AFI according to the gestational ages after being submitted to a smoothing process using the quadratic polynomial adjustments were shown in Chart (5). The range of the mean ± SD of the AFI increased from 118.32 ±0.4mm at the 14th week to a maximum of 147.16±0.09mm at the 24 th week of gestation.…”
Section: ) and Chart (3)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, renal length shows linear correlation with gestational age between 25-40 weeks. Both the Ruchi Saxena 12 and Manasvi et al 13 study showed that foetal renal length corresponds to gestational age in weeks, but in our study renal length corresponds to weeks only in 25 to 30 weeks of gestation. As the gestation age increases the renal length is more than corresponding gestation in our study, which is similar to many other studies.…”
Section: Discussioncontrasting
confidence: 63%
“…Thus, this study suggests 30 weeks was 30.88±1.36 mm, in Kansaria 29.03±1.32 mm, in Saxena et al 29.67±0.51 mm, and Konje it is 30.9±3.2 mm. In this study mean kidney length at 38 weeks was 39.7±2.36 mm in Kansaria 36.25±1.70 mm, in Saxena et al, 37.54±0.54 mm and Konje study 40±2.4 mm 15. …”
supporting
confidence: 44%